Pengaruh Kinerja Keuangan Terhadap Harga Saham di Masa Pandemic Covid-19 yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Siti Rustika Kalla; Suwito Suwito; Asrudin Hormati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
The objectives of this study are: To see the influence of financial performance on share prices during in the Covid-19 pandemic listed on the indonesian stock exchange. The population in this research is manufacturing companies, which are listed on the indonesian stock exchange in 2019-2021. The type of data use in this research is quantitavive data and the data analysis method used is descriptive statistical analysis. Then with the calssical assumption test, multicollinearity test, and heteroscedasity test. Hypothesis testing uses panel testing. The result of this research show that Return On Assets (ROA) has an effect on stock prices during the covid pandemic. The results of regression analysis state that ROE has no effect on stock prices. The results of the analysis of the ROS variable state that ROS has no effect on stock prices during the covid-19 pandemic. The results of analysis of the EPS variable show that earnings per share have no effect on share prices.